Effect of Group Cognitive-Behavioral Techniques Training on Social Anxiety in Nursing Students - Nahid Ramak; Ladan Moinefard; Paria Jangi; Alireza Sangani (Journal of Holistic Nursing and Midwifery)
Introduction:  Anxiety disorders are induced by cognitive and behavioral inefficiencies. Objective: The present study aimed to investigate the effect of group cognitive-behavioral training techniques on social anxiety in nursing students. Materials and Methods: This was a quasi-experimental study with a pretest-posttest follow-up (one month) and a control group design. The statistical population comprised all nursing students of Babol City, Iran. Fifty-four individuals diagnosed with social anxiety were selected using a simple random sampling method. The study groups were tested in three stages; before and after the intervention and follow-up, using the Liebowitz Social Anxiety questionnaire. The experimental group was subjected to 12 sessions of 60-minute under the group intervention of cognitive-behavioral therapy based on social anxiety. However, the control group received no training. Results: The obtained results suggested that cognitive-behavioral techniques training was effective on social anxiety. The mean social anxiety scores of the experimental and control groups were significantly different (P=0.004). Conclusion: Group training of cognitive-behavioral techniques significantly affected the social anxiety of studied students. Moreover, this study suggests the use of cognitive-behavioral group therapy to reduce the social anxiety of nursing students.